2017
DOI: 10.17700/jai.2017.8.2.376
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting mobile phone usage by the farmers in receiving information on vegetable cultivation in Bangladesh

Abstract: Mobile phone can reduce the transaction cost resulted in increasing the farm productivity. This paper mainly focuses on identifying the factors affecting the use of mobile phone by the farmers and determining the extent of use of mobile phone by the farmers in receiving information on vegetable cultivation. The study was carried out at three villages under Mymensingh sub- district of Mymensingh district in Bangladesh. Seventy farmers were interviewed using structured questionnaire during April 1 to May 1 2016.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 0 publications
3
29
0
Order By: Relevance
“…However, age of the farmers and farming experience had shown significant and negative relationship with their access to ICT based media. Similar results were found by Asif [16]. This is may be due to the reason that young people are always interested to ICTs compared to old farmers.…”
Section: Relationship Between the Selected Characteristics Of The Farsupporting
confidence: 86%
“…However, age of the farmers and farming experience had shown significant and negative relationship with their access to ICT based media. Similar results were found by Asif [16]. This is may be due to the reason that young people are always interested to ICTs compared to old farmers.…”
Section: Relationship Between the Selected Characteristics Of The Farsupporting
confidence: 86%
“…On the other hand, no significant relation was found between socioeconomic characteristics of large farmers and overall usage of online and mobile media. The results of the correlations corroborate the studies by Khan et al, [8] Asif et al, [9] and Hinduja et al [10], who reported similar findings.…”
Section: Relationship Between Online and Mobile Media Use And Varioussupporting
confidence: 90%
“…Better distribution of mass media can increase agricultural attractiveness and providing more information to stakeholder for increasing production (Rao, 2007). Mass media have potentiality to provide timely and reliable information on weather, input prices, and marketing of the products (Chapman and Slaymaker, 2002) Although a number of studies have already been conducted in Bangladesh on use of different mass media in technology transfer to farmers (Asif, 2016;Sharmin, 2013), study on effectiveness of these media particularly in agricultural area is scarcely available. However, no systematic study is available on the aspects of effectiveness of mass media in receiving technical information as well as technology transfer to the farmers.…”
Section: Introductionmentioning
confidence: 99%